Intra-Arterial Embolization as a Treatment Option in a Case of GAVE Syndrome - Soumil Singhal; Mangerira C. Uthappa (Journal of Clinical Interventional Radiology ISVIR)
Gastric antral vascular ectasia (GAVE) syndrome is a rare condition affecting the stomach. It is associated with upper gastrointestinal bleeding. The exact pathogenesis of the condition is poorly understood. Watermelon stomach is synonymous with GAVE syndrome due to its endoscopic appearance. Here we report a unique experience of performing an intra-arterial embolization in a case of GAVE presenting with uncontrolled bleeding.